2020
DOI: 10.1111/ijcp.13695
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and risk factors of recurrent pneumonia in children at Qena governorate, Egypt

Abstract: Background There is a scarce research study on recurrent pneumonia in children, particularly in the developing world. This study aimed to analyse the clinical characteristics, risk factors and underlying causes of recurrent pneumonia in children. Methods It was a case‐control study involved 87 children with ≥2 episodes of radiographically confirmed pneumonia in a single year or ≥3 episodes at any time with a radiographic clearing of densities between attacks. Controls were 87 age and gender‐matched children wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 26 publications
(57 reference statements)
6
19
2
Order By: Relevance
“…Underlying diseases were previously identified in 69%-92.4% of children with RP in different settings, which was similar to our results. [4][5][6][7][8][9][10][11]13 In accordance with most of these studies, we identified recurrent aspiration as the most common underlying condition. However, we found a higher prevalence of PID, BPD, and PCD and a lower prevalence of aspiration and asthma, compared with data from a study performed 20 years ago at a tertiary care pediatric hospital in Canada.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Underlying diseases were previously identified in 69%-92.4% of children with RP in different settings, which was similar to our results. [4][5][6][7][8][9][10][11]13 In accordance with most of these studies, we identified recurrent aspiration as the most common underlying condition. However, we found a higher prevalence of PID, BPD, and PCD and a lower prevalence of aspiration and asthma, compared with data from a study performed 20 years ago at a tertiary care pediatric hospital in Canada.…”
Section: Discussionsupporting
confidence: 79%
“…Among 551 patients, 90.6% were younger than 6 years of age; 66.4% were male; and 18.6% were born premature. The median age at first episode of pneumonia was 5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) months, and the median age at diagnosis of RP was 14 (8-37) months (Table 1). Overall, 483 (87.7%) patients were identified as having at least one underlying disorder, and the proportions of prematurity and low birth weight were significantly higher in patients with underlying diseases.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations